‘Tapestry’ – A Pink Fancy-Leaved Caladium Variety for Containers and Landscapes - Zhanao Deng (EDIS, 2011)
Move over ‘Carolyn Whorton’, there’s a new variety of fancy-leaved pink caladium coming on the scene. ‘Tapestry’ is intended for use in large containers and landscapes. This 5-page fact sheet was written by Zhanao Deng, and published by the UF Department of Environmental Horticulture, August 2011.